An action research approach to curriculum development - Phil Riding; Sue Fowell; Phil Levy (Information Research: An International Electronic Journal)
Action research has been used in many areas where an understanding of complex social situations has been sought in order to improve the quality of life. Among these are industrial, health and community work settings. Kurt Lewin, often cited as the originator of action research, used the methodology in his work with people affected by post- war social problems. Action research approaches to educational research were adopted in the late 60s and early 70s by the teacher- researcher movement in the secondary education sector. This sought to bring the practising classroom teacher into the research process as the most effective person to identify problems and to find solutions. We believe that an action research approach can contribute very positively to activity within the tertiary sector concerned with teaching quality issues, and with national Teaching Quality Assessment initiatives. As 'reflective practitioners', we can achieve greater ownership of the evaluative process by becoming systematically self-assessing, alongside, and feeding into, external assessment processes.